Sleep Disturbances and Mental Health Among Adolescents: A Cross-Sectional Study - Khairun Nisa; Susi Roida Simanjuntak; Suharno Usman (An Idea Nursing Journal, 2026)
Background: Sleep is essential for the physical, cognitive, and emotional development of adolescents. Despite its importance, sleep disturbances are increasingly prevalent in this population and may contribute to mental health problems. Objective: This study analyzed the relationship between sleep disturbances and mental health among adolescents Methods: Sleep disturbances and mental health were measured using the Sleep Disturbance Scale for Children (SDSC) and the Strengths and Difficulties Questionnaire (SDQ), respectively. Data analysis employed the Spearman rank correlation test. Results: Results indicated that 79.7% of adolescents experienced sleep disturbances, most frequently related to sleep–wake transitions (29.6%). Additionally, a considerable proportion demonstrated abnormal mental health profiles, with emotional (30.4%) and conduct problems (28.1%) being most prominent. Correlation analysis showed a statistically significant positive relationship between sleep disturbances and both total difficulties (r = 0.145, p = 0.007) and the hyperactivity subscale (r = 0.116, p = 0.031). Conclusion: These findings suggest that compromised sleep quality is closely associated with mental health problems in adolescents. In conclusion, sleep disturbances are significantly associated with mental health outcomes among adolescents in Manado. Addressing sleep quality, particularly sleep–wake transitions, may be a critical intervention to reduce psychological difficulties, underscoring the importance of targeted sleep hygiene programs in adolescent healthcare.